HS and Inflammation: A Potential Playground for the Sulfs? - El Masri, Rana; Crétinon, Yoann; Gout, Evelyne; Vivès, Romain R. (Frontiers in Immunology, 2020)
Heparan sulfate (HS) is a complex polysaccharide abundantly found in extracellular matrices and cell surfaces. HS participates in major cellular processes, through its ability to bind and modulate a wide array of signaling proteins. HS/ligand interactions involve saccharide domains of specific sulfation pattern. Assembly of such domains is orchestrated by a complex biosynthesis machinery and their structure is further regulated at the cell surface by post-synthetic modifying enzymes. Amongst them, extracellular sulfatases of the Sulf family catalyze the selective removal of 6-O-sulfate groups, which participate in the binding of many proteins. As such, increasing interest arose on the regulation of HS biological properties by the Sulfs. However, studies of the Sulfs have so far been essentially restricted to the fields of development and tumor progression. The aim of this review is to survey recent data of the literature on the still poorly documented role of the Sulfs during inflammation, and to widen the perspectives for the study of this intriguing regulatory mechanism towards new physiopathological processes.